2020
DOI: 10.1002/jbt.22448
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabonomics analysis of quercetin against the toxicity induced by cadmium in rats

Abstract: This study aimed to investigate the protective effect of quercetin against the toxicity induced by chronic exposure to low levels of cadmium in rats by an ultra performance liquid chromatography mass spectrometer. Rats were randomly divided into six groups as follows: control group (C), low dose of quercetin group (Q1: 10 mg/kg·bw), high dose of quercetin group (Q2: 50 mg/kg·bw), cadmium chloride group (D), low dose of quercetin plus cadmium chloride group (DQ1), and high dose of quercetin plus cadmium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…Kato et al treated rats with CdCl 2 at a low dose for 90 days and found that amino malonic acid was a biomarker for the toxicity of Cd alone [31]. Jia et al also found that quercetin could relieve Cd toxicity by regulating the metabolism of lipids and amino acids [32]. In this study, the effects of different foodborne forms of Cd treatment on serum metabolites were investigated.…”
Section: Discussionmentioning
confidence: 93%
“…Kato et al treated rats with CdCl 2 at a low dose for 90 days and found that amino malonic acid was a biomarker for the toxicity of Cd alone [31]. Jia et al also found that quercetin could relieve Cd toxicity by regulating the metabolism of lipids and amino acids [32]. In this study, the effects of different foodborne forms of Cd treatment on serum metabolites were investigated.…”
Section: Discussionmentioning
confidence: 93%
“…46 PC and phosphatidylethanolamine (PE) also play essential roles in the recognition and transduction of cell membrane signals, and they are hydrolyzed to generate LPC and LPE. 47 PC could protect neurons from the toxic effects of Aβ, 48 whereas LPC could inhibit LPS-mediated inflammatory responses and abnormal activation of microglia. 49 Therefore, HF improves the abnormal activation of microglia, reduces inflammation, and protects cell membranes by regulating phospholipid metabolism in AD mice.…”
Section: Discussionmentioning
confidence: 99%
“…39 It was also reported that quercetin protected liver and kidney function from cadmium-induced toxicity by regulating lipid and amino acid metabolism, thus enhancing the antioxidant defense system. 40 In addition, quercetin was shown to alter the metabolites of human umbilical vein endothelial cells incubated with high glucose or TNF-α towards a less inflamed phenotype, both alone and in the presence of pro-inflammatory stimulation. 41 In the present study, we identified 23 potential differential metabolites in the serum of DCM mice.…”
Section: Discussionmentioning
confidence: 99%
“…39 It was also reported that quercetin protected liver and kidney function from cadmium-induced toxicity by regulating lipid and amino acid metabolism, thus enhancing the antioxidant defense system. 40 In addition, quercetin was shown to alter the metabolites of human umbilical vein endo-…”
Section: Discussionmentioning
confidence: 99%